Hypercalcemia of Malignancy in a Patient with Hypoparathyroidism: A Complicated but Treatable Condition - Sierra, Marielly; Alvarado, Milliette; Ramírez, Margarita; González, Loida; Bueno, Solalba (Puerto Rico Health Sciences Journal, 2019)
Hypercalcemia in hypoparathyroidism has rarely been described. A 55 year-old male patient with primary hypoparathyroidism, left eye melanoma, and Noonan’s syndrome, was referred to the endocrinology clinics due to hypoparathyroidism. Laboratories showed serum calcium of 7.8 mg/d, and phosphate 4.8 mg/dl, while using calcium carbonate 1200 mg and vitamin D3 600 IU daily. Calcitriol 0.25 mcg daily was started and calcium carbonate discontinued. Abdominopelvic CT scan and thoracolumbar MRI, showed metastasis to liver, pancreas, and osteolytic lesions in spine, humerus, and ribs. Liver biopsy confirmed metastatic melanoma. Eight weeks later, serum calcium increased to 12 mg/dl. PTH, vitamin D 1,25-OH and PTHrP levels were within the lower range of normal compatible with hypercalcemia of malignancy, secondary to osteolytic disease. Zoledronic acid was added to treat hypercalcemia and bone pain. Our case demonstrates a successful treatment and monitoring of hypocalcemia after administration of bisphosphonate in a patient with hypoparathyroidism.